Clinical and laboratory indicators of polycystic ovary syndrome in Chinese Han nationality with different Rotterdam criteria-based phenotypes. (1st February 2016) - Zhao, Yue; Ruan, Xiangyan; Mueck, Alfred O.
Abstract: The aim of this study was to investigate the clinical, endocrinic and metabolic indicators in polycystic ovary syndrome (PCOS) with different Rotterdam criteria (RC)-based subtypes, thus to guide the treatments. Six hundred and forty-seven PCOS cases were divided into four groups, with 60 cases set as the control group, the clinical and endocrinic indicators of different subtypes were evaluated. Group A was the most common and the most serious (63.2%), while group B was the least (9%). The clinical signs, as well as the endocrinic and metabolic characteristics, of the two groups were similar, but group A exhibited higher androgen level and hirsutism score. The phenotypes of group C (15.6%) and group D (12.9%) were mild, but compared with the control group, luteinizing hormone (LH) and LH/follicle stimulating hormone (FSH) were significantly increased. Insulin resistance in these four subtypes were positively correlated with apolipoprotein B (ApoB)/apolipoprotein A1 (ApoA1), while only positively correlated with serum total testosterone, and negatively correlated with LH/FSH in group A. RC-PCOS typing could reflect the basic characteristics of the disease. Hyperandrogenism was the main basis for distinguishing PCOS, although the non-hyperandrogenism group could represent a relatively mild phenotype of PCOS, there might exist different pathogenic pathways.